Linking autophagy with inflammation through IRF1 signaling in ER+ breast cancer. (2nd January 2016) - Cook, Katherine L; Schwartz-Roberts, Jessica L; Baumann, William T; Clarke, Robert
Abstract : Resistance to antiestrogen therapy remains a critical determinant of mortality in patients affected by ER+ breast cancer. Our previous work identified autophagy and interferon regulatory factor 1 (IRF1) signaling as key regulators of this process. We have recently demonstrated a novel reciprocal interaction between IRF1 and ATG7, linking inflammation and autophagy.